Analysis of Deep Learning Approaches to Student Learning Experiences in Elementary Schools - Anis Binti Salamah; Dimas Dwi Andika; Siti Khodijah; Salwa Amirotul Hannan; Ulfia Wafiya Nurul; Frennanda Rahmadani; Nadya Nasywa Luthfiyah; Ainun Ayu Novyanti (Journal of Practice Learning and Educational Development, 2024)
This study aims to analyze the application of the learning process through a deep learning approach on student learning experiences in elementary schools using a descriptive qualitative research method. Data were obtained through interviews with teachers at SDIT Al Akbar who had implemented deep learning in schools, then the data were analyzed by reducing, presenting, drawing conclusions, and verifying the data. The results of the study found three main categories, namely: increased student learning engagement, increased critical and reflective thinking skills of students, and increased student self-confidence. The study concluded that deep learning not only enriches the learning process but also helps students develop higher-order thinking skills that are important for academic success and long-term development. These findings recommend the consistent and targeted application of deep learning strategies to improve the quality of student learning experiences in elementary schools.